Mapping of a Pale Green Mutant Gene and Its Functional Verification by Allelic Mutations in Chinese Cabbage (Brassica rapa L. ssp. pekinensis) - Zhao, Yonghui; Huang, Shengnan; Zhang, Meidi; Zhang, Yun; Feng, Hui (Frontiers in Plant Science, 2021)
Leaves are the main organ for photosynthesis, and variations in leaf color affect photosynthesis and plant biomass formation. We created two similar whole-plant pale green mutants (pem1 and pem2) from the double haploid (DH) Chinese cabbage line ‘FT’, through ethyl methanesulfonate (EMS) mutagenesis of seeds. Photosynthetic pigment contents and net photosynthetic rates were significantly lower in the mutants, than in the wild-type ‘FT’, and the chloroplast thylakoid endomembrane system was poor. Genetic analysis showed that the mutated phenotypes of pem1 and pem2 were caused by a single nuclear gene. Allelism tests showed that pem1 and pem2 were alleles. We mapped Brpem1 to a 64.25 kb region on chromosome A10, using BSR-Seq and map-based cloning of 979 F2 recessive individuals. Whole-genome re-sequencing revealed a single nucleotide polymorphism (SNP) transition from guanine to adenosine on BraA10g021490.3C in pem1, causing an amino acid shift from glycine to glutamic acid (G to E); in addition, BraA10g021490.3C in pem2 was found to have a single nucleotide substitution from guanine to adenosine, causing an amino acid change from E to lysine (K). BraA10g021490.3C is a homologue of the Arabidopsis divinyl chlorophyllide a 8-vinyl-reductase (DVR) gene that encodes 3,8-divinyl protochlorophyllide a 8-vinyl reductase, which is a key enzyme in chlorophyll biosynthesis. Enzyme activity assay and chlorophyll composition analysis demonstrated that impaired DVR had partial loss of function.